Atividade enzimática, trocas gasosas, produtividade e qualidade de frutos de mangueira pulverizada com CaCO3 e Si - Silva, Anderson Rodrigo Luciano da (2020)
The cultivation of mango trees (Mangifera indica L) at the São Francisco Valley Submediate is one of the most technologically advanced cultivation in Brazil. The edaphoclimatic conditions and its management system enable fruit production throughout the year. However, the elevated temperatures associated with the reduction of water lamina in the branches maturation phase have been causing excessive stress on mango trees. When exposed to stresses, the plants activate different protection mechanisms, among which the accumulation of low molecular weight organic solutes in the tissues is present. Throughout this, the present work aims to evaluate the effectiveness of silicon based protective membrane associated with calcium carbonate in the reducing abiotic stress of the mango tree cv. Palmer in the semi-arid region of Pernambuco. The experiment was developed in a 10-year-old commercial mango tree orchard in the city of Petrolina, Pernambuco, located in the Brazilian semiarid. The following treatments were evaluated: T1- Evidence; T2- Calcium Carbonate (5 kg / 100 L); T3- Humigel Plus A (500 ml/100 L); T4- Humigel Plus A (500ml/100 L) + calcium carbonate (5kg/100 L); T5 - Humigel Plus A (500 ml/100L) + Humigel Plus Si (2000 ml/100 L); and T6 - Humigel Plus A (2000 ml/100 L) which corresponds to the recommendedinduction. The experimental design was made in randomized blocks, then evaluated in subdivided plots. Were evaluated: carbohydrate metabolism (totalsoluble carbohydrates and cornflour); activity of antioxidant enzymes (ascorbateperoxidase, catalase, superoxide dismutase -SOD and - amylase); α-amilase); atividade photosyntheticactivity (stomatal conductance, transpiration, liquid photosynthesis rates, andinternal CO2 concentration); longitudinal and transverse diameter productioncomponents, leaf temperature, production (kg plant-1), productivity (t ha- 1); postharvest(post-harvest quality). The data were submitted to analysis of variance,and the means were compared to each other by the Tukey test at the level of 5%of probability using the R software. The total carbohydrate content showed a difference only at 5 DAA and 46 DAA, and at 4 DAA all treatments had had the highest carbohydrate content. For leaf cornflour contents, the peak for T1, T2, T3 and T4 was registered at 3 DAA, while T5 and T6 showed low increase on this date. The results of α-amilase); atividade-amylase did not show statistical differences between thetreatments on the evaluated dates, thus it is clear that for all treatments theyshowed an increase up to 4 DAA, with different behavior ia the subsequentevaluations. In relation to liquid photosynthesis, a significant increase was observed for all treatments at three days after application, except for the Evidence which remained practically stable. The activity of the enzyme ascorbate peroxidase (APX) was significantly affected by the application of treatments only on two evaluation dates (3 and 5 days after application of the treatments). The activity of the superoxide dismutase enzyme (SOD) showed a very significant oscillation basically for two treatments (T1 - Evidence, and T2 - calcium carbonate with 5 kg/100 L). The results indicate a clear action of the protective membrane in the attenuation of the vegetable stress of mango trees, including a persistent effect asa function of time, and considering the evaluated interval.